Improving occupational health for health workers in a pilot hospital by application of the HealthWISE international tool: An interview and observation study in China - Zhang, Min; Huang, Yiming; Wu, Fengyao; Liu, Dongmei; Wei, Caiyun; Qin, Yaqin (Frontiers in Public Health, 2022)
Objective For a safe and healthy workplace in the health sector, the International Labor Organization (ILO) and the World Health Organization (WHO) jointly developed HealthWISE, an international technical tool that helps health workers (HWs) to identify workplace hazards and apply low-cost solutions. This study sought to gather experiences and lessons from a Chinese pilot hospital for the scale-up application of HealthWISE. Methods A qualitative study was undertaken at a Chinese public hospital with a ≥5-year application of HealthWISE through in-depth interviews with targeted HWs who participated in the Training-of-Trainer (TOT) workshops, and observations were gathered using evidence from photos and publications, then, thematic analysis was formulated. Results Driven by motivation, the participants learned from the HealthWISE TOT workshop alongside the favorite and worst parts of it. Positive changes and results of occupational health for HWs occurred after the workshop, the participants trained others and planned to implement HealthWISE within their responsibility. During the COVID-19 Pandemic, the Hospital acted the approaches of protecting the health, safety and well-being of HWs with significant results. Further suggestions on workshop and HealthWISE implementing as well as the national policies were collected. The study indicated the Hospital's experience of leadership and participation, supporting and facilitating, system establishment, and culture creation. The suggestion included keeping staff engaged under a positive safety and health culture, promoting recognition of HealthWISE among public health institutions nationwide, developing online courses for medical colleges, focusing on the alignment among various law systems, and adopting measures under the principle of the hierarchy of occupational hazards controls. Conclusion This study has demonstrated the systematic improvement of occupational health for HWs by HealthWISE implementation in the Chinese hospital. The valuable experiences and lessons derived here can be shared with other hospitals in China and beyond, especially under the unprecedented challenges of the COVID-19 pandemic, to achieve the goals of safety, health, and well-being for HWs by building a resilient health system.